The Successful Scientific Periodicals: Contemporary Issues - B.V. Toshev (University of Sofia, 2014)
The new scientific results should be published. However, the scientific result will be lost in inappropriate choice of the media in which is expected to appear. The world periodicals are developed in two levels, parts of the World System of Abstracting, Indexing and Evaluation, WSAIE. This system is just the body of the world science. The first level consists of the primary research journals. After careful inspection these journals should be accepted for covering in secondary research sources; the latter build the second level of the system. Journals, which are not presented in secondary research sources, are considered as marginal and the submission of manuscripts to such journals is not recommended. The second level of WSAIE has an elite part, an American one (Thomson Reuters, Web of Science), and an European one (Elsevier, SCOPUS). The journals of Web of Science are characterized by their impact factor, IF; the journals of SCOPUS are characterized by their im-pact rank, SJR; these journals' scientometric characteristics are entirely equal in use; no one of them should be favoured in respect to the other. However, these factors characterize the journals, not authors publishing in them; there-fore, these numbers cannot be used neither to compare different scientific areas nor in the personal evaluation of authors' scientific activity. The personal and institutional competencies for research could be estimated by properly use of some scientometric variables. The most important of them are considered. Amongst them are the index of Hirsch, h, and the factor of efficiency, e. In twenty-first century a new development of science began. The researchers should know the features of the contemporary science policy; otherwise the traps of the new time would compromise the effort of the researcher to achieve a success in his/her research activity. The status and the new developments in world science are both discussed. The transition from the 'normal science' (Kuhn) to the 'post-normal science' (Funtowicz & Ravetz) is commented. The integration processes in science, the mass higher education and its mcdonaldization are also considered. The difference between science and surrogate science is explained. Finally, the present status of the Macedonian and Bulgarian chemistry (and of some other fields of science) is commented in comparative manner on the basis of data of the analytical section of SCOPUS.